UJI FUNGSIONALITAS (BLACKBOX TESTING) SISTEM INFORMASI LEMBAGA SERTIFIKASI PROFESI (SILSP) BATIK DENGAN APPPERFECT WEB TEST DAN UJI PENGGUNA - Febiharsa, Dhega; Sudana, I Made; Hudallah, Noor (Joined Journal (Journal of Informatics Education), 2018)
Information systems in an organization have an important role in providing information to management in order to control various complex processes within an organization. The implementation of information systems in the Batik Professional Certification Institute, can help the management of Batik LSP in controlling processes in organizations, ranging from participants, assessors, Competency Test Places, to scheduling competency tests. Information systems designed to build must be through a test before use. Information system testing is carried out to determine whether or not the application is suitable for use by users. This study aims to conduct a series of tests on information systems that have been designed to build. The method used is experimental, using the AppPerfect Web Test application and the Functional Test questionnaire (Black Box Testing) instrument provided to users. The purpose of this study, to determine the extent to which these two test methods can be reliable in testing the information system of professional certification institutions that are built. Based on the analysis carried out, the AppPerfect Web Test application is in line with the results of the function test by the user. In other words, functional testing can be done by users or with the AppPerfect Web Test application, or both.